2020
DOI: 10.3390/cancers12113413
|View full text |Cite
|
Sign up to set email alerts
|

Mutant Kras as a Biomarker Plays a Favorable Role in FL118-Induced Apoptosis, Reactive Oxygen Species (ROS) Production and Modulation of Survivin, Mcl-1 and XIAP in Human Bladder Cancer

Abstract: Tumor heterogeneity in key gene mutations in bladder cancer (BC) is a major hurdle for the development of effective treatments. Using molecular, cellular, proteomics and animal models, we demonstrated that FL118, an innovative small molecule, is highly effective at killing T24 and UMUC3 high-grade BC cells, which have Hras and Kras mutations, respectively. In contrast, HT1376 BC cells with wild-type Ras are insensitive to FL118. This concept was further demonstrated in additional BC and colorectal cancer cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 66 publications
(87 reference statements)
0
13
0
Order By: Relevance
“…Recent bladder cancer studies have shown that genetic mutations in bladder epithelial cells frequently occur in FGFR3 , PIK3CA , and RAS (all associated with RAS signaling networks) ( Bockorny et al, 2018 ; Tsujino et al, 2019 ). In addition, a 2020 study demonstrated that the RAS mutation can be a favorable biomarker for diagnosing cancer patients ( Santha et al, 2020 ). With regard to the relationship between RAS oncogene and microRNAs (miRNAs), accumulating evidence suggests that some miRNAs directly target RAS signaling pathways, thereby impeding RAS-driven tumorigenesis ( Jinesh et al, 2018 ; Ding et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent bladder cancer studies have shown that genetic mutations in bladder epithelial cells frequently occur in FGFR3 , PIK3CA , and RAS (all associated with RAS signaling networks) ( Bockorny et al, 2018 ; Tsujino et al, 2019 ). In addition, a 2020 study demonstrated that the RAS mutation can be a favorable biomarker for diagnosing cancer patients ( Santha et al, 2020 ). With regard to the relationship between RAS oncogene and microRNAs (miRNAs), accumulating evidence suggests that some miRNAs directly target RAS signaling pathways, thereby impeding RAS-driven tumorigenesis ( Jinesh et al, 2018 ; Ding et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with patients who died of sepsis, survivors also showed higher expression of lncRNA ENST00000504301.1, and lower expression of ENST00000452391.1 (104). Similarly, one study found that the expression of CRNDE was positively correlated with sequential organ failure assessment (SOFA), APACHEII score, and the expression of CRP and PCT (61).…”
Section: Lncrnas In Diagnosis and Prognosis Of Sepsismentioning
confidence: 94%
“…These results reflected the study of Sun et al (1992) (60) who also found that inhibiting CRNDE could alleviate sepsis-induced kidney injury by blocking the activation of TLR3/NF-kB signaling. However, the study by Wang et al demonstrated that overexpression of CRNDE could downregulate the expression of miR-181a-5p, thereby increased the expression of peroxisome proliferator activated receptor a (PPARa), and finally protected kidney from more severe injury through promoting cell proliferation and preventing cell apoptosis (61). It is worth mentioning that Chen et al and Wu et al discovered that HOTAIR was upregulated in LPS-induced septic mice, and promoted monocyte apoptosis via sponging miR-211 and increasing TNF-a production through p65/NF-kB pathway (35,38).…”
Section: The Roles Of Lncrnas In Sepsismentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, TP53/p53 mutations or KRAS mutations are well known to be challenging treatment resistant factors. However, FL118 exhibited better anticancer efficacy in colorectal cancer (CRC) cells with mutant p53 [ 176 ], and our recent studies indicated that FL118 exhibited even better anticancer efficacy either in human bladder cancer cells with KRAS mutation or in human CRC cells with KRAS mutation in comparison with bladder cancer cells or CRC cells with wild type KRAS [ 186 , 187 ].…”
Section: Could the Small Molecule Fl118 Or An Fl118 Analogue Be Developed For Rcc Treatment?mentioning
confidence: 99%